Mesin Ayak Dua Saluran Dilengkapi Pengarah untuk Produk Beras Jagung - Yohanes B Yokasing; Amiruddin Abdullah; Stanislaus Tamelab (Universitas Muhammadiyah Yogyakarta, 2022)
A sieve machine is used to separate groups of granules based on size. Most separation sieves on two groups of sifted/filtered grains move immediately, but the unfiltered grains are removed by the operator turning the sieve sideways or lifting the unfiltered material. In addition, the sifted material is usually poured directly on the sieve wire. This slows the sifting process, and the buildup can damage the sieve. On the other hand, sieve materials, such as corn rice products, require two sizes of sieve wire holes. Design, make, and study the function,